Partisipasi Anggaran Dan Kinerja Manajerial Melalui Psychological Capital & Persepsi Terhadapinovasi(Penelitian Empiris Pada Satuan Kerja Perangkat Daerah Di Provinsi DKI Jakarta) - Nurainun Bangun (Jurnal Akuntansi, 2017)
This study aimed to investigate the effect of budgetary participation on managerial performance in public sector organizations. This study also investigate whether Psychological Capital and perception on innovation mediate budgetary participation and managerial performance. The population in this study are all structural and staff at the regional work units (SKPD) of Jakarta. The samples taken were echelons of three and four and the staff at SKPD Jakarta. This study uses survey research methods to the collection of primary data using questionnaires. Selection of the samples were tested in this study using purposive sampling method. The data collected were processed using path analysis in Statistical Package for Social Science (SPSS 20) to test the effect of direct and indirect budgetary participation on manjerial performance. The results of this study showed that the direct effect of budgetary participation on managerial performance. Budgetary participationis also a significant influence on Psychological Capital. Psychological Capital and perception of innovation proved to mediate the relationship of budgetary participation and managerial performance.